Sinonim Adjektiva dalam Bahasa Minangkabau di Nagari Talang Babungo Kabupaten Solok - Zena Fransiscaluadia; Novia Juita (Persona: Kajian Bahasa dan Sastra, 2022)
This study aims to describe the level of synonymy of Minangkabau language adjective pairs based on the type of usage in Nagari Talang Babungo, Hiliran Gumanti District, Solok Regency. this type of research is qualitative research using descriptive method. The data of this research are utterances containing adjective synonyms in the Minangkabau language in the Talang Babungo village, Hiliran Gumanti District, Solok Regency. The source of the research data is pairs of synonymous adjectives, totaling 82 pairs. Data analysis in this study was carried out by working steps. First, analysis of meaning components, antonyms and substitutions.Second, identify the types level of synonyms of adjectives. Third, to conclude research data.In this study, four types of synonyms were found in the Minangkabau language in Nagari Talang Babungo, Solok Regency, namely absolute complete synonyms as many 41 pairs, complete not absolute as many 9 pairs, absolute incomplete as many 22 pairs and incomplete not absolute as many 10 pairs. The most dominant type of synonym found is absolute complete synonym.